Effects of canagliflozin on anaemia in patients with type 2 diabetes and chronic kidney disease: a post-hoc analysis from the CREDENCE trial. Issue 11 (November 2020) - Oshima, Megumi; Neuen, Brendon L; Jardine, Meg J; Bakris, George; Edwards, Robert; Levin, Adeera; Mahaffey, Kenneth W; Neal, Bruce; Pollock, Carol; Rosenthal, Norman; Wada, Takashi; Wheeler, David C; et al.
Summary: Background: Sodium-glucose co-transporter 2 inhibitors might enhance erythropoiesis and increase red blood cell mass. We assessed the long-term effects of canagliflozin on anaemia-related outcomes. Methods: In a post-hoc analysis of the Canagliflozin and Renal Events in Diabetes with Established Nephropathy Clinical Evaluation (CREDENCE) trial, we included patients with type 2 diabetes and chronic kidney disease who were randomly assigned to treatment with canagliflozin or placebo at 690 sites in 34 countries. We assessed the effects of canagliflozin versus matched placebo on haemoglobin and haematocrit using linear mixed-effects models. The primary outcome of this post-hoc analysis was a composite outcome of investigator-reported anaemia or treatment for anaemia, which was assessed using Kaplan-Meier analysis and Cox regression models. All analyses were done by intention to treat. Findings: Between March 24, 2014, and May 5, 2017, 4401 participants were randomly assigned to receive canagliflozin (100 mg; n=2202) or placebo (n=2199). At baseline, mean haemoglobin concentration was 132·0 g/L (SD 17·7), 1599 (36%) of 4401 participants had anaemia (defined as haemoglobin <130 g/L in men or <120 g/L in women), and 33 (<1%) of 4401 participants used erythropoiesis-stimulating agents. During a median follow-up period of 2·6 years (IQR 2·1–3·1), mean haemoglobin concentration was 7·1 g/L (95% CI 6·4–7·8) higher and haematocrit was 2·4% (2·2–2·6) higher in the canagliflozin group than the placebo group. Overall, 573 of 4401 participants had either an investigator-reported anaemia event or initiation of treatment for anaemia: 358 (8%) of 4401 participants reported anaemia events, 343 (8%) initiated iron preparations, 141 (3%) initiated erythropoiesis-stimulating agents, and 114 (2%) received blood transfusion. The risk of the composite outcome of anaemia events or initiation of treatment for anaemia was lower in the canagliflozin group than the placebo group (hazard ratio 0·65, 95% CI 0·55–0·77; p<0·0001). Compared with the placebo group, participants in the canagliflozin group also had lower risks of anaemia events alone (0·58, 0·47–0·72; p<0·0001), initiation of iron preparations (0·64, 0·52–0·80; p<0·0001), and need for erythropoiesis-stimulating agents (0·65, 0·46–0·91; p=0·012). Interpretation: These data suggest that canagliflozin reduces the risk of anaemia-associated outcomes, including the need for erythropoiesis-stimulating agents, among patients with type 2 diabetes and chronic kidney disease. Funding: Janssen Research and Development.